Real effects of relaxing financial constraints for homeowners: Evidence from Danish firms - Alessia De Stefani; Julia Moertel (Danmarks Nationalbank, 2019)
We study how a reduction in financial constraints faced by homeowners affects consumption, and in turn employment creation and the skill composition of the workforce over the business cycle. We leverage a wide set of Danish administrative registries, and implement a difference-in-differences strategy based on the introduction of a new mortgage product in 2003 to estimate the causal effect of a relaxation of homeowners' borrowing constraints on consumer expenditure. The estimated exogenous shift in consumption, which varies across municipalities and over time, is a strong predictor of the growth in employment for local establishments. However, the positions created due to a credit-induced demand shock differ from pre-trends: they require lower skill levels and are filled by younger, less experienced and less educated workers. These workers, particularly those filling low-skilled positions between 2004 and 2007, face earlier separations and a higher degree of unemployment ex-post.
Keywords: E32; D22; J21; 330; Mortgages; consumption; employment